Brain gain: claims about its size and impact on welfare and growth are greatly exaggerated - Maurice Schiff (Institute for the Study of Labor (IZA), 2005)
Based on static partial equilibrium analysis, the new brain drain literature argues that, by raising the return to education, a brain drain generates a brain gain that is, under certain conditions, larger than the brain drain itself, and that such a net brain gain results in an increase in welfare and growth due to education's positive externalities. This paper, on the other hand, argues that these claims are exaggerated. In the static case, and based on both partial and general equilibrium considerations, the paper shows that i) the size of the brain gain is smaller than suggested in that literature; ii) the impact on welfare and growth is smaller as well (for any brain gain size); iii) a positive brain gain is likely to result in a smaller human capital gain and may even have a negative impact on the stock of human capital; iv) an increase in the stock of human capital may have a negative impact on welfare and growth; and v) in a dynamic framework, the paper shows that the brain drain is unambiguously larger than the brain gain, i.e., that the steady state is characterized by a net brain loss.
Keywords: D61; D62; F22; H20; H41; I12; J61; 330; brain gain size; welfare; growth; exaggerated claims; Brain Drain; Wohlfahrtstheorie; Wirtschaftswachstum; Theorie